2000
DOI: 10.1093/brain/123.9.1863
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal patterns of breathing during swallowing in neurological disorders

Abstract: Swallowing momentarily inhibits breathing, and normally the great majority of apnoeas which accompany a swallow are followed by expiration (xE swallows). This swallowing-breathing interaction is regarded as one of several mechanisms by which the airway is protected from aspiration during swallowing. The purpose of this study was to investigate the interaction of breathing and swallowing in two groups of neurological patients. Twenty-two patients with defined neurological disorders involving various structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 26 publications
3
72
1
Order By: Relevance
“…There is some evidence that choking may occur only with solids in some neuromuscular patients [28]. However, water rather than jelly was used in most of the previous studies [12,13,27,29], which allowed us to compare our results with earlier data. Furthermore, the use of solids requires chewing, which may cause fatigue, thereby worsening the swallowing impairments.…”
Section: Study Limitationsmentioning
confidence: 83%
“…There is some evidence that choking may occur only with solids in some neuromuscular patients [28]. However, water rather than jelly was used in most of the previous studies [12,13,27,29], which allowed us to compare our results with earlier data. Furthermore, the use of solids requires chewing, which may cause fatigue, thereby worsening the swallowing impairments.…”
Section: Study Limitationsmentioning
confidence: 83%
“…(2) what are characteristics of oropharyngeal swallowing disorders in patients with COPD? (3) what are the risk factors for developing oropharyngeal swallowing disorders in patients with COPD, and (4) is there any evidence that standard medical treatments for COPD improve oropharyngeal swallowing safety?…”
Section:  Introductionmentioning
confidence: 99%
“…Most investigations that have examined the effects of disordered respiration on swallowing have studied patients with neurologic disease [3][4][5][6][7] . These studies have examined the interaction between disordered breathing and its effect on swallowing in patients with motor neuron disease 3 , spastic cerebral palsy 5 , and Parkinson's disease 6 . Interestingly, only one study sought to compare the breathing and swallowing performance in those with neuromuscular disease and in those with respiratory failure with tracheotomy 4 .…”
mentioning
confidence: 99%
“…These findings are consistent with a role for brainstem control (Nishino and Hiraga 1991), especially as both the respiratory center and the swallowing CPG are located in the same area of the brainstem. In contrast, other studies demonstrated that the cortex influences breathing-swallowing interactions in unconscious patients (Hadjikoutis, Pickersgill et al 2000). In the other direction, alterations in breathing patterns and ventilation may influence the coordination of swallowing and breathing.…”
Section: Interaction Between Respiration and Swallowingmentioning
confidence: 91%
“…Aspiration is another important consequence of impaired swallowing that becomes increasingly common as the disease progresses (Finder, Birnkrant et al 2004). To the best of our knowledge, breathing-swallowing interactions initially received little research attention (Hadjikoutis, Pickersgill et al 2000). Moreover, improvements in the management of chronic respiratory failure translate into differences in breathing conditions across patients and over time, and this variability is likely to complicate the evaluation of breathing-swallowing interactions.…”
Section: Breathing-swallowing Interaction In Neuromuscular Patientsmentioning
confidence: 99%